Indian Mosque, Trinidad, West Indies - (:unkn) unknown (Pereira and Co., Ltd., Trinidad, 2010)
This is a coloured photograph of the Mohammed Jinnah Memorial mosque in St. Joseph, Trinidad and Tobago. Postcard number P77560.
Colour: Coloured; Style: Landscape; Other: Unbordered, Divided.
Keywords: Trinidad and Tobago; Postcards; Mosques--Trinidad and Tobago; Church buildings--Trinidad and Tobago; Islamic architecture--Trinidad and Tobago; Architecture, Asian--Trinidad and Tobago